PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN PARTISIPASI DAN PRESTASI BELAJAR (Studi Pada Muatan Pelajaran IPS di Kelas V SD Kecamatan Dempo Utara Kota Pagar Alam) - Marlina Widya Ningsih (DIADIK, 2021)
This study aims to describe the application of the cooperative learning model type of Snowball Throwing to increase student participation and learning achievement in the fifth grader on social studies subject at SD Negeri Dempo Utara District. The research design used was classroom action research and quasi-experimental. The research subjects were fifth grade students of SD Negeri 41 Pagar Alam of the 2020/2021 school year. Simple Random Sampling was used to determine the quasi-experimental sample, they were the fifth grader of SD Negeri 26 Pagar Alam and class fifth grader of SD Negeri 25 Pagar Alam. The research instrument used observation sheets and tests. The research data were analyzed using descriptive statistics, mean (mean), percentage, and t-test. The results showed that the application of the Snowball Throwing, one of cooperative learning model could increase the participation and learning achievement of the fifthgrade students of SD Negeri in Dempo Utara District.